ULUL ALBAB DALAM TAFSIR FI ZHILAL AL-QUR’AN KITAB TAFSIR SAYYID QUTHB - M. Taib Hunsouw (TAHKIM, 2017)
One of the great Sayyid Qutb’s works is Tafsir Fi Zhilal al-Qur'an which has adabi patterns or literature and preaching. One verse that becomes the author concentration of his tafsir is the ulul albab verses meaning “the owner of the doors” or who has brain or mind that concentrate to Allah. "Of 16 verses containing Ulul albab only seven verses are reviewed in this article. Of course his study on Ulul Albab is not exhaustive him but from other meanings existed in his tafsir is envisaged that people who use their brains in the way of Allah and read the signs of Allah both kauniyah and qauliyah are those the ulul albab. Instead though use the reason but do not has purpose and lead to Allah it is not called the ulul albab as hinted at the end of the Surah Ali-Imran verse 191. Keywords: Ulul albab, interpretation of the Koran